Functional and Language Features of Nicknames of German-Speaking Users of Humorous Internet Sites - Zakharova, Elena Valerevna (Razvitie obrazovaniâ (Online), 2020)
The author of the article outlines that nicknames represent a relatively new linguistic phenomenon in virtual communication, which has been the subject of many contemporary studies. However, some aspects of this phenomenon, as well as the spheres of the Internet in which nicknames function, remain insufficiently explored. The aim of the work is to solve the question whether nicknames of users of entertainment sites have special structural, semantic and functional features that distinguish them from users of other resources. To solve the above-mentioned question an attempt to identify and describe the features of nicknames of only one specific area – German-language humorous websites has been made by the author of the article. Methods. In the course of the research, the following methods were applied: structural analysis, statistical method, descriptive method, observation, comparison, generalization, systematization and interpretation, as well as the method of quantitative experimental data processing. Results of the research. In the course of the research more than 200 nicknames were collected and analyzed according to various criteria: by their language affiliation, by structural and semantic methods of their creation, by age and gender of the users. The author supposes that nicknames should be considered in the context of the particular Internet resources, as the discursive specificity of sites determines, first of all, the semantic feature of nicknames. It is emphasized that the main function of humorous websites is humor and entertainment, so the dominant motives for creating nicknames will be laughter and principled lightness. The author also pays special attention to the fact that unlike other types of nicknames, humorous virtual names are not intended to arouse interest and sympathy, but perform primarily identifying and pragmatic functions.